Optimal Control and Cost-Effectiveness Analysis in An Epidemic Model with Viral Mutation and Vaccine Intervention - Adi, Yudi Ari; Irsalinda, Nursyiva; Ndii, Meksianis Z (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2022)
This paper introduces an optimal control problem in a two-strain SIR epidemic model with viral mutation and vaccine administration. The purpose of this study was to investigate the efficacy and cost-effectiveness of two disease prevention strategies, namely restriction of community mobility to prevent disease transmission and vaccine intervention. We consider the time-dependent control case, and we use Pontryagin’s Maximum Principle to derive necessary conditions for the optimal control of the disease. We also calculate the Average Cost-Effectiveness Ratio (ACER) and the Incremental Cost-Effectiveness Ratio (ICER) to investigate the cost-effectiveness of all possible strategies of the control measures. The results of this study indicate that the most cost-effective disease control strategy is a combination of mobility restriction and vaccination.